2005
DOI: 10.1111/j.1365-2559.2005.02300.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased annexin I expression in prostatic adenocarcinoma and in high‐grade prostatic intraepithelial neoplasia

Abstract: Expression of annexin I inversely correlates with the increasing histological grade of prostatic adenocarcinoma. By showing a progressive loss of annexin I expression in high-grade PIN, intermediate-grade and high-grade cancer, our findings suggest that the loss of annexin I expression occurs early in prostatic tumorigenesis and becomes more prominent throughout tumour progression. The loss of expression of annexin I may serve as a useful marker of prostate cancer development and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 14 publications
2
33
0
1
Order By: Relevance
“…Annexin I is involved in many biological functions such as cell differentiation[36], anti-inflammation[37], apoptosis[38], and cell growth[39], and acts as a stress protein[40]. Decrease or loss of annexin I expression in a number of cancer types including breast[41], prostate[42,43], lymphoma[44], esophageal[42,45] and bladder[4] cancers has been reported recently, indicating annexin I may serve as a useful marker of cancer development and progression. Annexin I was also reported to be degraded in bronchoalveolar lavage fluid from patients with cystic fibrosis, and is therefore considered to be related to lung inflammation[46].…”
Section: Discussionmentioning
confidence: 99%
“…Annexin I is involved in many biological functions such as cell differentiation[36], anti-inflammation[37], apoptosis[38], and cell growth[39], and acts as a stress protein[40]. Decrease or loss of annexin I expression in a number of cancer types including breast[41], prostate[42,43], lymphoma[44], esophageal[42,45] and bladder[4] cancers has been reported recently, indicating annexin I may serve as a useful marker of cancer development and progression. Annexin I was also reported to be degraded in bronchoalveolar lavage fluid from patients with cystic fibrosis, and is therefore considered to be related to lung inflammation[46].…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of controversy still exists regarding the expression of ANXA1 in different types of cancers. Several studies have shown that the expression of ANXA1 is down-regulated in cervical, breast, head and neck, or thyroid cancer [16], [17], [18], [19], [20]. On the other hand, there is also some evidence that an increase of ANXA1 expression has occurred in other types of cancer, such as pancreatic, esophageal, and gastric carcinomas [21], [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…Together, these studies suggest that dysregulation of annexin A1 loss is important in oesophageal tumour development and progression. Other types of cancer in which the expression of annexin A1 has been shown to be altered include pancreatic adenocarcinoma (Bai et al, 2004), where it was found to show increased expression in the majority of tumours, renal cell carcinoma (Zimmermann et al, 2007), prostate adenocarcinoma (Patton et al, 2005), breast cancer (Shen et al, 2006) and B-cell non-Hodgkin's lymphoma (Vishwanatha et al, 2004).…”
mentioning
confidence: 99%